2011
DOI: 10.1177/1359105311427475
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in long term breast cancer survivors: relation to coping, social support and cognitive processing

Abstract: Post-traumatic growth (PTG) has rarely been studied in long term breast cancer survivors using open interviews. In order to address the issue of how women integrate PTG in their overall cancer experience, 28 open interviews concerning changes after cancer were carried out with 5- to 15-year survivors. The analysis of results, performed using Alceste software, revealed one thematic class of PTG which was specific to women with high coping and social support and active cognitive processing. PTG theme appeared mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
2
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 44 publications
9
75
2
5
Order By: Relevance
“…The PTG levels reported in the current sample were comparable with PTG reports from other studies with similar populations (Cordova et al, 2007;Danhauer et al, 2013;Lelorain et al, 2012). These findings may suggest that different manifestations of stress should be considered differently in cancer care, and tests of the PTG model (Tedeschi & Calhoun, 2004;Tedeschi et al, 1998) should include assessments of both linear and non-linear associations between stress and challenges and PTG.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The PTG levels reported in the current sample were comparable with PTG reports from other studies with similar populations (Cordova et al, 2007;Danhauer et al, 2013;Lelorain et al, 2012). These findings may suggest that different manifestations of stress should be considered differently in cancer care, and tests of the PTG model (Tedeschi & Calhoun, 2004;Tedeschi et al, 1998) should include assessments of both linear and non-linear associations between stress and challenges and PTG.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, in the context of cancer, PTG would be dependent on the degree of stress experienced in relationship to the cancer diagnosis, cancer treatment, and/or cancer-related lifestyle changes. In studies validating the PTG model, qualitative and quantitative analyses, and reviews of the existing scholarship, researchers have suggested a potential positive association between prolonged psychological stress and increased PTG among survivors of cancer (Lelorain et al, 2012;Sabiston et al, 2007). However, the nature and directionality of this relationship is still poorly understood in this population, with some studies reporting positive (Lechner et al, 2003;Sears et al, 2003), negative (Love & Sabiston, 2011;Tomich & Helgeson, 2004) or null (Manne et al, 2004;Weiss, 2004) relationships between psychological stress and PTG.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cabe pensar que una relación de pareja que aporta apoyo de calidad fomenta el CPT de forma muy parecida a como lo hace el soporte social. De hecho, la gran mayoría de artículos asocian de forma directa el soporte social y el CPT (e.g., Lelorain, Tessier, Florin, & Bonnaud-Antignac, 2012). Otro factor psicosocial muy relacionado con el desarrollo de CPT y el soporte social es la afiliación religiosa.…”
Section: Calidad De Vidaunclassified
“…En cuanto a variables típicamente asociadas a un funcionamiento psicológico positivo en la Ppos, como son el optimismo, la esperanza, afecto positivo y la calidad de vida tampoco muestran consenso, encontrándose prácticamente la misma cantidad de artículos a favor y en contra de su relación con el CPT (Casellas-Grau, Vives, Font, & Ochoa, 2016). Sin embargo, sí parece haber consenso en cuanto a la relación directa entre bienestar y CPT en los cuatro estudios que la estudiaron (Danhauer et al, 2013;Lelorain et al, 2012;Olden, 2009;Ruini & Vescovelli, 2012). Finalmente, dos estudios que han estudiado conceptos próximos a los de bienestar y su relación con el CPT, como son la felicidad (Lelorain, Bonnaud-Antignac, & Florin, 2010) y la gratitud (Ruini, Vescovelli, & Albieri, 2013), encuentran, también, una relación directa.…”
Section: Calidad De Vidaunclassified